Pengaruh Kompensasi dan Motivasi terhadap Kinerja Pegawai PT. Satu Bintang - Hariri, Imaduddin (Jurnal Flight Attendant, 2024)
The purpose of this research is to determine the effect of compensation and motivation on employee performance. This research uses a survey method with a questionnaire as the instrument. The respondents for this research were 55 employees at PT Satu Bintang. The sampling process uses a non-probability sampling technique using an associative quantitative approach using primary data. The data analysis technique used is SPSS version 20. These results show that compensation has a positive and significant effect on employee performance with a calculated t value greater than the t table. Motivation has a positive and significant effect on employee performance where the calculated t value is greater than the t table.